2020
DOI: 10.17479/jacs.2020.10.2.42
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Impact of Abdominal Surgery on Delirium in Abdominal Trauma Patients

Abstract: Purpose: The occurrence of trauma-related delirium following postoperative abdominal surgery is associated with a poor prognosis. The purpose of this study was to identify predictive risk factors for trauma-related delirium. Methods: Trauma patient data from a regional trauma center were retrospectively collected from August 2015 to December 2016. The primary inclusion criteria were patients diagnosed with traumarelated delirium following abdominal trauma surgery. Head trauma patients and those under 18 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
(11 reference statements)
1
5
0
Order By: Relevance
“…This study showed that age was a risk factor for delirium in trauma pa ents which is similar to the study by a Roh et al and Bryczkowsko et al This is because advancing age pa ents have co-morbidi es, physiological changes, metabolic disturbances, and altera on in the level of the neurotransmi er in the brain which predisposes the pa ent to delirium. 2,7 Long standing hypertension was iden fied as a risk factor in our study which is similar to the study by a Kim et al Hypertension can be associated with a decline in cogni ve performance. The vascular damage exposes hypertensive pa ents to cerebral hypo perfusion and cerebral hypoxia and makes them at risk for delirium when admi ed in the ICU.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study showed that age was a risk factor for delirium in trauma pa ents which is similar to the study by a Roh et al and Bryczkowsko et al This is because advancing age pa ents have co-morbidi es, physiological changes, metabolic disturbances, and altera on in the level of the neurotransmi er in the brain which predisposes the pa ent to delirium. 2,7 Long standing hypertension was iden fied as a risk factor in our study which is similar to the study by a Kim et al Hypertension can be associated with a decline in cogni ve performance. The vascular damage exposes hypertensive pa ents to cerebral hypo perfusion and cerebral hypoxia and makes them at risk for delirium when admi ed in the ICU.…”
Section: Discussionsupporting
confidence: 90%
“…Delirium is an acute brain dysfunc on and studies have shown that the incidence of delirium in the trauma pa ents in the intensive care unit (ICU) is between12.5% to 67%depending upon the type, the severity of the trauma, and a diagnos c method used. [2][3][4][5] Seda on management and delirium assessment is a rou ne procedure in our ICU by trea ng physicians and ICU staff. The nurse performs and records the result of seda on and delirium by using Richmond Agita on-Seda on Scale (RASS) and confusional assessment method (CAM-ICU) for every pa ent admi ed in the intensive care unit twice a day and whenever a pa ent experiences a change in mental status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that the length of stay in the ICU was higher in delirious patients that is similar to other studies. 4,5,9,10 Length of stay causes more economic burden to patients and family members can cause more hospital-acquired infections and psycho-social problems.…”
Section: Discussionmentioning
confidence: 99%
“…1 Delirium is an acute brain dysfunction and studies have shown that an incidence of delirium in the surgical intensive care unit (ICU) is between3.6% to 73% depending upon the severity of the illness, type of surgery, and the diagnostic method used. [2][3][4][5][6][7][8] The onset is usually over 1-2 days and can deteriorate further with poor prognosis if appropriate intervention is delayed.…”
Section: Introductionmentioning
confidence: 99%